Labor Supply Dynamics, Unemployment and Human Capital Investments - Etienne Wasmer (Institute for the Study of Labor (IZA), 2002)
In the last decades, the OECD labor markets faced important labor supply changes with the arrival of women and the cohorts of the baby-boom. Using a survey where workers declare their true employment experience, this paper argues that these supply trends imply more inexperienced workers. It then investigates the important consequences of this fact on the skill composition of the labor force, between-groups wage inequality and the level of unemployment. The main result is that a labor market with wage rigidities may not recover from such a temporary labor supply shock: with a younger and less experienced labor force, there is higher unemployment among low-experience workers, they do not accumulate enough on-the-job human capital, this reduces in the long-run the supply of skilled (experienced) workers and the demand for unskilled workers. This intertemporal multiplication of supply shocks generates multiple equilibria, and the rigid economy is stuck to the bad equilibrium even after the shock. In a competitive market, in contrast, wage inequality and notably, the wage return to experience becomes higher but there is no persistence of the supply shock. Higher education prevents this intertemporal multiplication of supply shocks.
Keywords: J31; J21; E24; 330; Wage inequality; education; experience; labor supply; Arbeitsangebot; Schock; Arbeitsmarkttheorie; Qualifikation; Theorie der Arbeitslosigkeit; Bildungsinvestition; Lohnstruktur; Lohnrigidität; Arbeitsmarktflexibilisierung; Theorie; Frankreich; Berufserfahrung